Labour Migration and Remittance Use: Determinants and Their Effects on Farm Households in Selected Areas of Bogura District in Bangladesh (Journal of the Bangladesh Agricultural University, 2024)
The present study was conducted to analyze various socio-economic aspects of households with migrant and non migrant, influencing factors of labour migration and the impact of remittance on agricultural production. This study was conducted in two upazilas of Bogra districts namely Gabtoli and Shahjahanpur. The study areas were selected purposively. A sample of 60 respondents was being chosen purposively; 30 from households with migrant and 30 from households without migrant. Logistic regression model was used to measure the influencing factors of labour migration. Educational level of household head, household size, land size and household higher educated person of the selected household had a significant impact on labour migration in the research areas though the land of the household had a negative impact on labour migration. Descriptive statistics were used to measure the impact of remittance of the household with migrant. The average annual agricultural income (crop farming) of household with migrant is higher than household without migrant. The migration had brought positive changes in different types of livelihood assets. This study recommends that policy makers should create a more enabling economic environment and to provide procedural and structural support to the migrant workers to accrue the benefits of labour migration in relation to the country’s overall development.J Bangladesh Agril Univ 19(1): 119–127, 2021https://doi.org/10.5455/JBAU.21576